Global Immunometabolic Profiling of AECOPD. Issue 12 (26th October 2020) - Song, Dongli; Liu, Fangming; Zhu, Bijun; Yin, Jun; Kuang, Zhongshu; Dong, Zhimin; Yan, Lei; Ye, Ling; Zhang, Yong; Song, Zhenju; Wu, Duojiao; Wang, Xiangdong
Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is a major public health issue. In the study, mass cytometry is used with extensive antibody panels to perform in‐depth immune profiling of samples from patients with AECOPD, acute lung infection(AI) and healthy controls. Immune composition of 11 populations including CD4/CD8 T cells, B cells, NK cells, and others is identified. Significantly, 7 T cell subsets are changed among the three groups. Then RNA sequencing at single cell level is further processed to provide a detailed peripheral T cell immunity of AECOPD. Combined analysis suggests that dysfunctional effector T cells in AECOPD are characterized with suppressed mitochondria, dampened mTOR activity, and IFN‐γ production. Furthermore, targeting mTOR pathway synergized the PD‐1 blockade therapy promotes T cell glycolysis and IFN‐γ production. The study presents an in‐depth immunometabolic atlas of AECOPD. Abstract : High‐parametric single‐cell mapping of the peripheral blood mononuclear cell (PBMC) of patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) reveals altered immune cell subsets in AECOPD and metabolic restriction of AECOPD‐imposing T cells with dampened glycolytic capacity, and IFNgamma production, thereby allowing poor defense capacity to infection or exacerbation.